EFEKTIVITAS PELAKSANAAN BIMBINGAN BELAJAR DALAM MENGATASI KESULITAN BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMP BAHRUL HUDA SUMBER LANCAR LARANGAN TOKOL TLANAKAN PAMEKASAN - Shohibul Fatah; M Sahibudin (Journal of Education Partner, 2023)
The implementation of tutoring is an activity carried out to help solve the problems faced by students in learning so that they can learn independently and learn better so that the planned teaching and learning goals can be achieved more effectively. The focus of the research is 1) What is the effectiveness of implementing tutoring in overcoming students' learning difficulties in Islamic Religious Education subjects?, 2) What are the supporting and inhibiting factors in implementing tutoring in overcoming learning difficulties in Islamic Religious Education in Bahrul Huda Current Source of the Tlanakan Tokol Prohibition Pamekasan?, This type of research is a type of research with descriptive qualitative methods. The data collection technique that the author uses is through observation, interviews and documentation. The primary data source in this research is the guidance and counseling teacher with secondary data being the students themselves. The results of the research show that firstly, the implementation of tutoring in overcoming students' learning difficulties in Islamic religious education subjects at Bahrul Huda Middle School Sumber Lancar Prohibition of Tokol Tlanakan Pamekasan is effective. This can be seen from the increase in students' understanding of Islamic religious knowledge, students can manage their study time wisely. good and can improve student learning outcomes. Second, the supporting factors can be seen from the teacher's motivation and the students' high learning enthusiasm. Meanwhile, the inhibiting factors in implementing tutoring are the lack of facilities and infrastructure that support learning activities, such as the school environment and also the lack of awareness among students about the existence of formal education.